2022
DOI: 10.1155/2022/2381063
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life and Surgical Outcome of Transoral Endoscopic Thyroidectomy Vestibular Approach (TOETVA) versus Open Thyroid Surgery: Experience from a Single Center in Vietnam

Abstract: Background. It has been widely assumed that TOETVA has demonstrated a new technique and a promising approach as it is both minimally invasive and optimally cosmetic. The objective of this study was to assess the surgical outcome, aesthetic satisfaction, and postoperative quality of life of TOETVA in comparison with open thyroid surgery. Patients and Methods. The study was designed as a prospective study, in which 121 patients from a single center in Vietnam underwent thyroid surgery, and the study was divided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 33 publications
0
21
0
Order By: Relevance
“…Only two previous studies have utilized a questionnaire having a component on swallowing related dysfunction after thyroid surgery. Nguyen et al 8 22 used SF-12 and a self-developed thyroid surgery questionnaire which had a single question on dysphagia (Have you had any swallowing difficulties?). Authors reported no difference in this domain between TOETVA and OTx at the end of 6 weeks.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Only two previous studies have utilized a questionnaire having a component on swallowing related dysfunction after thyroid surgery. Nguyen et al 8 22 used SF-12 and a self-developed thyroid surgery questionnaire which had a single question on dysphagia (Have you had any swallowing difficulties?). Authors reported no difference in this domain between TOETVA and OTx at the end of 6 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Only two previous studies have utilized a questionnaire having a component on swallowing related dysfunction after thyroid surgery. Nguyen et al 8 . reported that TOETVA was superior to open surgery in terms of postoperative quality of life, patient satisfaction, and cosmetic outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Seventeen studies, 8,10,34,[37][38][39][40][41][42][43][44][45][46][48][49][50][51] including 2866 patients, reported data of postoperative pain and hospital stay (Figure 2E,F). The mean pain score varied from 2.08 to 3.76 in the TOETVA group, 1.67 to 3.13 in the TORT group, and 1.67 to 4.90 in the CTT group.…”
Section: Surgical Outcomesmentioning
confidence: 99%